To find the factor, we will transform the equation in the binomials. We must find two number that will multiply to equal -8 and will add to equal 2. You can do this by dividing -8 by its greatest common factor. The GCF and the answer from the division would be the two numbers needed.
-8 / 8 = -1
-8 / 4 = -2
-8 / 2 = -4
From doing that I can see when I divide -8 by 4 it gives me -2. -2 plus 4 equals 2.
-2 + 4 = 2
Also when multiply the two numbers it gives -8.
-2 + 4 = -8
So the two number are -2 and 8. Now we transform them into binomials. That would be:
(x - 2) and (x + 4)
Those are the two factors for x^2 + 2x - 8 = 0
So the answer is (x - 2)(x + 4) = 0